2018
DOI: 10.1039/c8ra04422h
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap engineering of a lead-free defect perovskite Cs3Bi2I9through trivalent doping of Ru3+

Abstract: Inorganic defect halide compounds such as Cs3Bi2I9 have been regarded as promising alternatives to overcome the instability and toxicity issues of conventional perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 40 publications
9
55
0
Order By: Relevance
“…Moreover, they pointed out that P true3¯ m 1 symmetry is the key to achieve highly efficient lead‐free perovskite solar cells with trivalent metal ions. In 2018, Peng et al obtained Ru 3+ ‐doped Cs 3 Bi 2 I 9 single crystals by the hydrothermal method and found that the direct and indirect bandgap values of Cs 3 Bi 2 I 9 (2.07 and 1.98 eV) could be reduced to 1.98 and 1.81 eV, respectively, as shown in Figure c,d. Besides, I − ion was employed to substitute Br − in layered Cs 3 Bi 2 Br 9 , and the researcher found the bandgap reduced to 2.05 from 2.66 eV in the layered Cs 3 Bi 2 Br 3 I 6 .…”
Section: Ternary Bismuth Halidesmentioning
confidence: 99%
“…Moreover, they pointed out that P true3¯ m 1 symmetry is the key to achieve highly efficient lead‐free perovskite solar cells with trivalent metal ions. In 2018, Peng et al obtained Ru 3+ ‐doped Cs 3 Bi 2 I 9 single crystals by the hydrothermal method and found that the direct and indirect bandgap values of Cs 3 Bi 2 I 9 (2.07 and 1.98 eV) could be reduced to 1.98 and 1.81 eV, respectively, as shown in Figure c,d. Besides, I − ion was employed to substitute Br − in layered Cs 3 Bi 2 Br 9 , and the researcher found the bandgap reduced to 2.05 from 2.66 eV in the layered Cs 3 Bi 2 Br 3 I 6 .…”
Section: Ternary Bismuth Halidesmentioning
confidence: 99%
“…Hong et al predicted theoretically In(III) might be better performer compare to Ga(III) as conduction band minimum of Cs 3 Bi 2−x In x I 9 shows well developed extended states between Bi‐I and In‐I bond . Doping of Ru(III) also results in decrease in band gap of Cs 3 Bi 2 I 9 and also narrowed optical bandgap, induced shallow defect states, and more radiative recombination centres …”
Section: Bismuth Perovskitesmentioning
confidence: 99%
“…[75] Doping of Ru(III) also results in decrease in band gap of Cs 3 Bi 2 I 9 and also narrowed optical bandgap, induced shallow defect states, and more radiative recombination centres. [76]…”
Section: Bismuth Perovskitesmentioning
confidence: 99%
“…Recently, Ru was used to partially replace Bi in Cs 3 Bi 2 I 9 to regulate its band gap and defect states by using a hydrothermal method. The Ru‐doped Cs 3 Bi 2 I 9 showed a narrowed band gap along with a considerable color change from bright to dark red with increasing doping level (Figure c) . In addition, the dopant‐induced shallow defect states and enhanced phonon–electron coupling lead to an overall upshift of the band structure, indicating a promising way to tune the optoelectronic properties of the defective Bi‐based material by partial element substitution.…”
Section: Bandgap Engineeringmentioning
confidence: 99%
“…c) Photos of samples of Cs 3 Bi 2 I 9 showing darkenedc olor with increasing Ru 3 + doping. Reprinted with permissionfrom Ref [55]…”
mentioning
confidence: 99%